Bringing the State Back into the favelas of Rio de Janeiro : Understanding Changes in Community Life after the UPP Pacification Process - World Bank (Washington, DC, 2013)
For many years, Rio de Janeiro has held the dubious distinction of being one of the world s most beautiful cities, and at the same time, one of the most dangerous. This report is the story of Rio s attempt to break with history and establish a new kind of state presence in its favelas. This report documents how life in the favelas is changing as a result of the Police Pacification Unit (UPP) pacification effort, as seen through the eyes of favela residents themselves. This study used a qualitative, case-study approach and consisted of observations, focus groups, and key informant interviews in four favelas. The study fits into the broader territorial approach to urban and social development that the World Bank has been supporting in both the state and city of Rio de Janeiro, and for which the historical alliance between federal, state and municipal governments in Rio has been crucial. These projects have focused on strengthening planning and management of urban growth in the metropolitan region, promoting the provision of affordable housing with access to infrastructure and service, and supporting the implementation of a targeted, comprehensive social development program for the urban poor. Under the social development agenda, the Bank has been providing support to Social UPP since its design stage, in 2010, through technical assistance services to strengthen social governance and territorially-based monitoring and evaluation.